Identification of the critical levels, sufficiency ranges and potential response to nutrient fertilization in vineyards by the DRIS method - Melo, G. W.; Rozane, D. E. [UNESP]; Brunetto, G. (International Society for Horticultural Science (ISHS), 2018)
Brazil is a significant global grape producer (Vitis spp.). The state of Rio Grande do Sul produces 59% of the national output. Despite the large national production, the grapevine has not yet been tested sufficiently to obtain data from long-term experiments in both production as well as suitable nutritional management. The DRIS method is one of the useful tools required to assess plant quality. The normal nutrient ranges were determined from 63 commercial fields, in order to interpret the concentrations of N, P, K, Ca, Mg, S, B, Cu, Fe, Mn and Zn in the culture through statistical analysis and regression. The DRIS indices were related to the respective contents present in the leaf dry matter samples collected during the veraison and opposite to the first bunch of the fruiting branch. Although the general index of the nutritional balance of the DRIS did not permit the establishment of a relationship with productivity, it enabled, based on the standards, the determination of the normal ranges for the nutrients evaluated. The results were in accordance with those reported in the literature. The potential response to fertilization was proven ineffective as an interpretive methodology.
Keywords: Foliar diagnosis; Mineral nutrition; Nutritional balance; Vitis spp.